EFFECTS OF METHOXYACETIC ACID (MAA) AND MAA-TREATED INTERNAL ENVIRONMENT OF THE DAMS ON THE QUALITY OF PREIMPLANTATION AND THE VIABILITY OF POSTIMPLANTATION SWISS WEBSTER MOUSE EMBRYOS (MUS MUSCULUS) - Ibrahim, Mustamin
Abstract The study to observe the effects of MAA on the development of preimplantation mouse embryos and MAA-treated internal environment of the dams on the viability of postimplantation mouse embryos had been conducted. The effects of MAA on the preimplantation embryos development was studied by administering MAA dose 2.0 mmollkg body weight (bw) by gavage on gestation day 1, whereas the control group was given distilled water in the same volume. Observation on the number of 1-cell, 2-cell, 3-to-8 cell, uncompacted morula, compacted morula, early blastocyst, late blastocyst and abnormal embryos were done on gestation day 3. Total number of cells, which composed late blastocyst was counted on gestation day 3.5 using Tarkowski\'s method (1966). Effects of MAA on the viability of postimplantation embryos were studied by surgically transferring the early blatocysts from treated and control groups into the uterus of day 2 pseudopregnant females. Effects of internal environment of the dams were studied by surgically transferring the early blastocysts from untreated female to the uterus of recipients that have been treated with MAA on day 1 of pseudopregnancy, and were observed on gestation day 16. Female recipients that have been treated with distilled water were used as control. The results showed that MAA could decrease the number of embryos that reached late blastocysts significantly (p<0.01). It was mainly caused by the increasing number of retarded embryos, especially inhibition of embryos development at the early blastocyst stage. Besides, the number of abnormal embryos was increased significantly (p<0.05). The decreasing quality of preimplantation embryos was also shown by the decreasing cell number (p<0.01) composing late blastocysts, and the result of embryo transfer study that showed a tendency of decreasing percentage of implantation and significantly (p<0.05) decreased the survival rate of the transferred embryos. The administration of MAA to the recipient mice significantly decreased (p<0.05) the percentage of implantation and the survival rate of transferred embryo. The viability of the embryos tended to decrease, either from MAA-treated embryos or from MAA-treated dams. This was shown by a tendency of decreasing percentage of survival rate of fetuses,caused by increasing percentage of intrauterine death. It could be concluded that MAA could directly decrease the quality and inhibit the development of preimplantation embryos. Besides, the MAA-treated internal environment of the uterus could decrease significantly the percentage of implantation and the viability of postimplantation embryos.